A cartilage regeneration composite scaffold and its preparation method and application
By filling the porous scaffold with photosensitive collagen and modified oxidized polysaccharides to form a composite scaffold, the problem of insufficient performance of existing cartilage regeneration materials is solved, and effective and rapid regeneration and repair of cartilage is achieved.
Patent Information
- Application Number
- CN202411935886.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
There is still room for improvement in existing cartilage regeneration materials in terms of biocompatibility, mechanical properties and degradation rate, and it is difficult to effectively and quickly repair cartilage defects.
Hydrogels formed by photosensitive collagen and modified oxidized polysaccharides are filled in the porous scaffold to form a composite scaffold, combining excellent biocompatibility, degradability and mechanical properties.
The composite scaffold gradually degrades in the body, promoting the regeneration and repair of cartilage, and its mechanical properties are close to natural cartilage, adapting to the internal environment, and improving the repair effect.
Smart Images

Figure CN119746161A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a cartilage regeneration composite scaffold and a preparation method and application thereof. Background Art
[0002] Knee cartilage defects are a common clinical disease, which are mainly manifested by knee dysfunction, severe pain, and even disability. Due to the avascular nature of articular cartilage and the limited regenerative capacity of chondrocytes, the cartilage has poor healing ability after injury, resulting in the defect site being usually filled with fibrous tissue with low biomechanical properties. The mechanical properties of this fibrous cartilage are significantly lower than those of normal hyaline cartilage, which often leads to osteoarthritis (OA) and causes long-term pain and joint dysfunction. Therefore, the effective treatment of cartilage defects has always been a major challenge facing clinicians and researchers.
[0003] In recent years, tissue engineering technology has made some progress in cartilage repair. The development of bionic artificial cartilage has become a breakthrough. These new materials can simulate the mechanical properties and biological characteristics of normal cartilage, providing an effective repair solution. Using 3D printing technology, scaffolds that match the patient's joint morphology can be accurately manufactured and combined with biomaterials to achieve personalized cartilage repair. The application of 3D printing technology has shown significant advantages in the field of tissue engineering. (1) Precision printing: It can print complex scaffold structures to ensure a perfect match with the patient's joint morphology; (2) Material combination: Multiple materials can be used at the same time to meet different mechanical properties and biocompatibility requirements; (3) Personalized repair: Design and manufacture personalized repair scaffolds according to the specific needs of the patient to enhance the treatment effect.
[0004] However, in current treatment technologies, there is still a need to improve the performance of cartilage regeneration materials, and existing materials still have room for improvement in terms of biocompatibility, mechanical properties and degradation rate. Summary of the Invention
[0005] The present invention aims to address at least one of the aforementioned technical problems existing in the prior art. To this end, the present invention provides a composite scaffold comprising a porous scaffold filled with a hydrogel formed from photosensitive collagen and modified oxidized polysaccharides. The resulting composite scaffold exhibits excellent biocompatibility and degradability, as well as superior mechanical properties, facilitating cartilage tissue regeneration and repair.
[0006] The second aspect of the present invention is to provide a method for preparing a composite stent.
[0007] The third aspect of the present invention is to provide an application of a composite stent.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] A first aspect of the present invention provides a composite scaffold, comprising a scaffold and a hydrogel; the raw materials for preparing the hydrogel include photosensitive collagen and modified oxidized polysaccharide; the hydrogel is filled in the scaffold.
[0010] The composite scaffold of the present invention combines the advantages of good biocompatibility and degradability of photosensitive collagen and modified oxidized polysaccharides, and combined with the scaffold, not only does the composite scaffold have excellent biocompatibility and degradability, but it can also promote the regeneration and repair of cartilage while gradually degrading in the body. In addition, the presence of the scaffold gives the composite scaffold a certain mechanical performance basis, and after further compounding with the hydrogel, the mechanical properties of the composite scaffold are closer to the mechanical properties of natural cartilage, and can better adapt to the in vivo environment. Therefore, the composite scaffold material of the present invention can repair cartilage damage sites, has the advantages of biocompatibility, degradability, high compressive strength, and can promote cartilage, which is conducive to the effective and rapid regeneration of cartilage defects.
[0011] In some embodiments of the present invention, the mass ratio of the photosensitive collagen to the modified oxidized polysaccharide is (0.1-10): (0.1-20).
[0012] In some embodiments of the present invention, the mass ratio of the photosensitive collagen to the modified oxidized polysaccharide is (0.5-10):(1-10).
[0013] In some specific embodiments of the present invention, the mass ratio of the photosensitive collagen to the modified oxidized polysaccharide is (0.5-1.5): (1-10).
[0014] In some specific embodiments of the present invention, the mass ratio of the photosensitive collagen to the modified oxidized polysaccharide is 1:(4-6).
[0015] The hydrogel formed by photosensitive collagen and modified oxidized polysaccharide has a significant impact on the biocompatibility and degradability of the composite scaffold material. The present invention is beneficial to regulating the biocompatibility and degradability of the hydrogel by adjusting the ratio of photosensitive collagen and modified oxidized polysaccharide.
[0016] In some embodiments of the present invention, the photosensitive collagen includes at least one of methacrylated collagen and glycidyl methacrylated collagen; and the collagen includes at least one of animal-derived collagen, type I collagen, type II collagen, and type III collagen.
[0017] In some embodiments of the present invention, the modified oxidized polysaccharide includes at least one of modified oxidized hyaluronic acid, modified oxidized chondroitin sulfate, modified oxidized chitosan, and modified oxidized sodium alginate.
[0018] In some embodiments of the present invention, the modifying agent for modifying the oxidized polysaccharide includes at least one of dopamine (DA) and methacrylic acid.
[0019] In some embodiments of the present invention, the modified oxidized polysaccharide is prepared by a method comprising the following steps: oxidizing the polysaccharide and then mixing it with a modifier for modification to obtain the modified oxidized polysaccharide.
[0020] In some embodiments of the present invention, after the polysaccharide is oxidized, a cross-linking agent is added during the modification process; the cross-linking agent includes at least one of glutaraldehyde, N,N'-methylenebisacrylamide, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), and N-hydroxysuccinimide (NHS).
[0021] In some embodiments of the present invention, the oxidizing agent for polysaccharide oxidation comprises sodium periodate.
[0022] In some embodiments of the present invention, the polysaccharide oxidation is carried out for an oxidation time of 1 to 3 hours.
[0023] In some embodiments of the present invention, after the polysaccharide is oxidized, a neutralization step is further included; the neutralization reagent includes ethylene glycol; and the neutralization time is 2 to 4 hours.
[0024] In some embodiments of the present invention, after the polysaccharide is oxidized, the modification time is 23 to 25 hours.
[0025] In some specific embodiments of the present invention, the modification is performed under alternating vacuum and nitrogen atmospheres.
[0026] In some embodiments of the present invention, the photosensitive collagen is prepared by a method comprising the following steps: mixing collagen with a double bond modifier to react to obtain the photosensitive collagen; the double bond modifier comprises at least one of methacrylic anhydride and glycidyl methacrylate.
[0027] In some embodiments of the present invention, the collagen and the double bond modifier are reacted in an ice bath for 23 to 25 hours.
[0028] In some embodiments of the present invention, the mixing reaction further includes dialysis and freeze-drying steps.
[0029] In some embodiments of the present invention, the scaffold is a 3D printed scaffold.
[0030] In some embodiments of the present invention, the compressive strength of the stent is 0.1 to 50 MPa.
[0031] In some embodiments of the present invention, the compressive strength of the stent is 1 to 5 MPa.
[0032] In some embodiments of the present invention, the composition of the scaffold includes at least one of polylactic acid (PLA), polycaprolactone (PCL), polylactic-co-glycolic acid (PLGA), polyglycolic acid (PGA), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), poly-β-hydroxyalkanoate (PHBA), and polycitric acid (POC).
[0033] Using the above polymer as the raw material of the scaffold has better mechanical properties.
[0034] The second aspect of the present invention provides a method for preparing the composite stent according to the first aspect of the present invention, comprising the following steps:
[0035] The photosensitive collagen and the modified oxidized polysaccharide are mixed and subjected to an enzyme cross-linking reaction; the mixture obtained by the enzyme cross-linking reaction is injected into a stent and subjected to a photoreaction to obtain the composite stent.
[0036] In some embodiments of the present invention, the photosensitive collagen and the modified oxidized polysaccharide are mixed in a PBS solution.
[0037] In some embodiments of the present invention, the mass fraction of the photosensitive collagen in the PBS solution is 0.1-5%; the mass fraction of the modified oxidized polysaccharide in the PBS solution is 0.1-20%.
[0038] In some specific embodiments of the present invention, the mass fraction of the photosensitive collagen in the PBS solution is 0.5-2%; the mass fraction of the modified oxidized polysaccharide in the PBS solution is 1-8%.
[0039] In some specific embodiments of the present invention, the mass fraction of the photosensitive collagen in the PBS solution is 0.5-2%; the mass fraction of the modified oxidized polysaccharide in the PBS solution is 4-6%.
[0040] In some embodiments of the present invention, the wavelength of illumination for the photoreaction is 365-420 nm.
[0041] In some embodiments of the present invention, the wavelength of light illumination for the photoreaction is 400-410 nm.
[0042] In some embodiments of the present invention, the light reaction time is 30s to 40min.
[0043] In some embodiments of the present invention, the light reaction time is 30s to 2min.
[0044] In some embodiments of the present invention, the time of the enzymatic cross-linking reaction is 30 seconds to 30 minutes.
[0045] In some embodiments of the present invention, the enzyme cross-linking reaction time is 1 to 3 minutes.
[0046] In some embodiments of the present invention, the cross-linking agent of the enzymatic cross-linking reaction includes at least one of peroxidase, transglutaminase, lysine oxidase, and hydrogen peroxide.
[0047] In some embodiments of the present invention, the photoreaction photoinitiator includes at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP), 2-hydroxy-2-methyl-1-phenyl-1-propanone, and phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide.
[0048] The third aspect of the present invention provides a use of the composite scaffold described in the first aspect of the present invention or the composite scaffold obtained by the preparation method described in the second aspect of the present invention in preparing a cartilage regeneration material.
[0049] The present invention improves the mechanical properties of the composite scaffold, making it closer to the mechanical properties of natural cartilage, thereby better adapting to the in vivo environment. It also enhances the biocompatibility of the composite scaffold material, reduces immune rejection after implantation, and improves the repair effect. Furthermore, the composite scaffold material promotes cartilage regeneration, promoting the proliferation and differentiation of chondrocytes. Therefore, the composite scaffold material of the present invention is particularly suitable for preparing cartilage regeneration materials. The use of the composite scaffold material can help alleviate pain caused by cartilage damage, improve patients' quality of life, reduce the need for joint replacements and cartilage transplants, and reduce medical costs.
[0050] In addition, how to better meet the individual differences in cartilage repair solutions is also one of the problems that the existing technology needs to solve. During the preparation process of the composite scaffold material of the present invention, the degradation rate of the composite scaffold material can be regulated by adjusting the conditions of the photoreaction and enzyme cross-linking reaction to meet the repair needs of different individuals.
[0051] Compared with the prior art, the present invention has at least the following beneficial effects:
[0052] (1) The cartilage regeneration composite scaffold provided by the present invention utilizes photosensitive collagen and modified oxidized polysaccharides to form a hydrogel filled in the scaffold, which gives the composite scaffold material excellent biocompatibility and degradability, and can be safely degraded in the body without causing adverse reactions. The presence of the scaffold provides a good mechanical performance foundation, so that the obtained composite scaffold material has excellent mechanical properties and can provide the necessary structural support. At the same time, the biological activity of the modified oxidized polysaccharide can promote cell adhesion and proliferation. Therefore, the composite scaffold of the present invention helps the growth and differentiation of chondrocytes on the hydrogel scaffold, and helps the regeneration and repair of cartilage tissue.
[0053] (2) The present invention is simple and easy to operate. It combines controllable photoreaction and enzyme cross-linking reaction, and injects photosensitive collagen and modified oxidized polysaccharide into the scaffold to achieve the preparation of hydrogel and its composite with the scaffold. By controlling the conditions of photoreaction and enzyme cross-linking reaction, the cross-linking degree and degradation rate of the hydrogel can be regulated, thereby meeting different cartilage repair needs and providing personalized effective solutions.
[0054] (3) The composite scaffold of the present invention has excellent biocompatibility, degradability and mechanical properties, and can be used to regulate the degradation properties of the material by adjusting the preparation conditions to form a personalized repair plan. It can be widely used in the preparation of biomedical materials, especially in the repair and regeneration of cartilage damage. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 The figures and scanning electron microscope images of the hydrogel, scaffold and composite scaffold in Example 1, Comparative Example 1 and Comparative Example 2 are shown; wherein, Figure 1 (a) is a diagram showing the actual curing effect of the hydrogel in Comparative Example 1; Figure 1 (b) is an electron micrograph of the hydrogel of Comparative Example 1; Figure 1 (c) is a physical image and electron microscope image of the PLGA scaffold of Comparative Example 2; Figure 1 (d) is a physical image and electron microscope image of the composite bracket of Example 1.
[0056] Figure 2 This is a compression strength test diagram of the composite bracket in Example 1.
[0057] Figure 3 This is the in vivo degradation diagram of the composite scaffold in Example 1.
[0058] Figure 4 This is a diagram showing the cell compatibility test of the composite scaffold in Example 1. DETAILED DESCRIPTION
[0059] The present invention is further described in detail below using specific examples. Unless otherwise specified, the raw materials, reagents, and apparatus used in the examples and comparative examples are available from conventional commercial sources or by conventional methods. Unless otherwise specified, all experimental or testing methods are conventional in the art.
[0060] The following describes the details in conjunction with specific embodiments and comparative examples.
[0061] Example 1
[0062] A cartilage regeneration composite scaffold includes a 3D printed PLGA (polylactic-co-glycolic acid) scaffold and a hydrogel; the hydrogel raw materials include photosensitive collagen (methacryloyl-type I collagen) and modified oxidized hyaluronic acid.
[0063] The preparation method of the composite stent comprises the following steps:
[0064] (1) Dissolve type I collagen in acetic acid solution, then add methacrylic anhydride dropwise and react in an ice bath for 24 hours; dialyze and freeze-dry to obtain methacryloyl-collagen (COL-MA);
[0065] (2) Hyaluronic acid and sodium periodate were dissolved in water to obtain a mixed solution, which was reacted at room temperature for 2 h, and ethylene glycol was added dropwise and neutralized for 3 h. After the reaction, the mixture was centrifuged, washed several times with ethanol and deionized water, and dialyzed and freeze-dried to obtain oxidized hyaluronic acid (OHA). OHA was dissolved in deionized water, and EDC, NHS, and DA solutions were added dropwise. The mixture was reacted under alternating vacuum and nitrogen atmosphere for 24 h to obtain modified oxidized polysaccharide (OHA-DA).
[0066] (3) COL-MA was dissolved in PBS, and then OHA-DA solution was added to the COL-MA solution. After mixing evenly, a mixed solution of photosensitive collagen and modified oxidized polysaccharide was obtained. LAP (phenyl (2,4,6-trimethylbenzoyl) phosphate lithium salt), HRP enzyme, and H2O2 were added dropwise while stirring. After stirring for 2 minutes, the mixed solution was injected into the 3D printed PLGA scaffold and irradiated under 405nm purple light for 1 minute to obtain the cartilage regeneration composite scaffold in this example (denoted as PLGA / COL-MA / OHA-DA); wherein, the mass percentage of COL-MA in the mixed solution of photosensitive collagen and modified oxidized polysaccharide was 1%, and the mass percentage of OHA-DA was 5%.
[0067] Example 2
[0068] A cartilage regeneration composite scaffold includes a 3D-printed PLA (polylactic acid) scaffold and a hydrogel; the hydrogel raw materials include photosensitive collagen (methacrylated type I collagen) and modified oxidized hyaluronic acid; the hydrogel is filled in the scaffold.
[0069] The preparation method of the composite stent comprises the following steps:
[0070] (1) Dissolve type I collagen in acetic acid solution, then add glycidyl methacrylate dropwise to obtain a mixed solution, then add methacrylic acid dropwise, and react in an ice bath for 24 hours; dialyze and freeze-dry to obtain methacrylated collagen (COL-GMA);
[0071] (2) Hyaluronic acid and sodium periodate were dissolved in water to obtain a mixed solution, which was reacted at room temperature for 2 h, and ethylene glycol was added dropwise and neutralized for 3 h. After the reaction, the mixture was centrifuged, washed several times with ethanol and deionized water, dialyzed, and freeze-dried to obtain oxidized hyaluronic acid (OHA). OHA was dissolved in deionized water, and EDC, NHS, and DA solutions were added dropwise. The mixture was reacted under vacuum and nitrogen alternately for 24 h to obtain dopamine-modified oxidized polysaccharide (OHA-DA).
[0072] (3) COL-GMA was dissolved in PBS, and then OHA-DA solution was added to the COL-GMA solution. After mixing evenly, a mixture of photosensitive collagen and modified oxidized polysaccharide was obtained. LAP, HRP enzyme, and H2O2 were then added dropwise while stirring. After stirring for 2 minutes, the mixed solution was injected into the 3D-printed PLA scaffold and irradiated under 405nm purple light for 3 minutes to obtain the cartilage regeneration composite scaffold in this example (denoted as PLA / COL-GMA / OHA-DA). Among them, the mass percentage of COL-GMA in the photosensitive collagen and modified oxidized polysaccharide mixture was 1%, and the mass percentage of OHA-DA was 5%.
[0073] Example 3
[0074] A cartilage regeneration composite scaffold includes a 3D-printed PCL (polycaprolactone) scaffold and a hydrogel; the hydrogel raw materials include photosensitive collagen (methacryloyl-type II collagen) and modified oxidized hyaluronic acid; the hydrogel is filled in the scaffold.
[0075] The preparation method of the composite stent comprises the following steps:
[0076] (1) Dissolve type II collagen in acetic acid solution, then add methacrylic anhydride dropwise and react in an ice bath for 24 hours; dialyze and freeze-dry to obtain methacryloyl-collagen (COL2-MA);
[0077] (2) Hyaluronic acid and sodium periodate were dissolved in water to obtain a mixed solution, which was reacted at room temperature for 2 h, and ethylene glycol was added dropwise and neutralized for 3 h. After the reaction, the mixture was centrifuged, washed several times with ethanol and deionized water, dialyzed, and freeze-dried to obtain oxidized hyaluronic acid (OHA). OHA was dissolved in deionized water, and EDC, NHS, and DA solutions were added dropwise. The mixture was reacted under vacuum and nitrogen alternately for 24 h to obtain dopamine-modified oxidized polysaccharide (OHA-DA).
[0078] (3) COL2-MA was dissolved in PBS, and then OHA-DA solution was added to the COL-MA solution. After mixing evenly, a mixture of photosensitive collagen and modified oxidized polysaccharide was obtained. LAP, HRP enzyme, and H2O2 were then added dropwise while stirring. After stirring for 2 minutes, the mixed solution was injected into the 3D-printed PCL scaffold and irradiated under 405nm purple light for 1 minute to obtain the cartilage regeneration composite scaffold in this example (denoted as PCL / COL2-MA / OHA-DA). Among them, the mass percentage of COL2-MA in the photosensitive collagen and modified oxidized polysaccharide mixture was 0.5%, and the mass percentage of OHA-DA was 6%.
[0079] Example 4
[0080] A cartilage regeneration composite scaffold includes a 3D-printed PHBV (poly(3-hydroxybutyrate-co-3-hydroxyvalerate)) scaffold and a hydrogel; the hydrogel raw materials include photosensitive collagen (methacryloyl-type I collagen) and modified oxidized chondroitin sulfate; the hydrogel is filled in the scaffold.
[0081] The preparation method of the composite stent comprises the following steps:
[0082] (1) Dissolve type I collagen in acetic acid solution, then add methacrylic anhydride dropwise and react in an ice bath for 24 hours; dialyze and freeze-dry to obtain methacryloyl-collagen (COL-MA);
[0083] (2) Chondroitin sulfate and sodium periodate were dissolved in water to obtain a mixed solution, and the mixture was reacted at room temperature for 4 hours. After the reaction was completed, the mixture was dialyzed and freeze-dried to obtain oxidized chondroitin sulfate (OChS). OChS was dissolved in deionized water, and EDC, NHS and MA (methyl acrylate) solution were added dropwise. The mixture was reacted under vacuum and nitrogen alternately for 4 hours to obtain polymethacrylated oxidized chondroitin sulfate (OChS-MA).
[0084] (3) COL-MA was dissolved in PBS, and then OChS-MA solution was added to the COL-MA solution. After mixing evenly, a mixture of photosensitive collagen and modified oxidized polysaccharide was obtained. LAP and transglutaminase were then added dropwise while stirring. After stirring for 5 minutes, the mixed solution was injected into the 3D-printed PHBV scaffold and irradiated under 405nm violet light for 2 minutes to obtain the cartilage regeneration composite scaffold in this example (denoted as PHBV / COL-MA / OChS-MA); wherein the mass percentage of COL-MA in the photosensitive collagen and modified oxidized polysaccharide mixture was 1.2%, and the mass fraction of OChS-MA was 8%.
[0085] Example 5
[0086] A cartilage regeneration composite scaffold includes a 3D-printed POC (polycitric acid) scaffold and a hydrogel; the hydrogel raw materials include photosensitive collagen (methacrylylated type I collagen) and modified oxidized sodium alginate; the hydrogel is filled in the scaffold.
[0087] The preparation method of the composite stent comprises the following steps:
[0088] (1) Dissolve type I collagen in acetic acid solution, then add methacrylic anhydride dropwise and react in an ice bath for 24 hours; dialyze and freeze-dry to obtain methacryloyl-collagen (COL-MA);
[0089] (2) Sodium alginate and sodium periodate were dissolved in water to obtain a mixed solution, and the mixture was reacted at room temperature for 4 hours. After the reaction was completed, the mixture was dialyzed and freeze-dried to obtain oxidized sodium alginate (OSA). OSA was dissolved in deionized water, and EDC, NHS and MA (methyl acrylate) solution were added dropwise. The mixture was reacted under vacuum and nitrogen alternately for 4 hours to obtain polymethacrylated oxidized sodium alginate (OSA-MA).
[0090] (3) COL-MA was dissolved in PBS, and then OSA-MA solution was added to the COL-MA solution. After mixing evenly, a mixture of photosensitive collagen and modified oxidized polysaccharide was obtained. LAP and lysine oxidase were then added dropwise while stirring. After stirring for 3 minutes, the mixed solution was injected into the 3D-printed POC scaffold and irradiated under 405nm purple light for 30 seconds to obtain the cartilage regeneration composite scaffold in this example (denoted as POC / COL-MA / OSA-MA); wherein the mass percentage of COL-MA in the photosensitive collagen and modified oxidized polysaccharide mixture was 0.8%, and the mass fraction of OSA-MA was 1%.
[0091] Comparative Example 1
[0092] A composite hydrogel, the preparation method of which comprises the following steps:
[0093] (1) Dissolve type I collagen in acetic acid solution, then add methacrylic anhydride dropwise and react in an ice bath for 24 hours; dialyze and freeze-dry to obtain methacryloyl-collagen (COL-MA);
[0094] (2) Hyaluronic acid and sodium periodate were dissolved in water to obtain a mixed solution, which was reacted at room temperature for 2 h, and ethylene glycol was added dropwise and neutralized for 3 h. After the reaction, the mixture was centrifuged, washed several times with ethanol and deionized water, dialyzed, and freeze-dried to obtain oxidized hyaluronic acid (OHA). OHA was dissolved in deionized water, and EDC, NHS, and DA solutions were added dropwise. The mixture was reacted under vacuum and nitrogen alternately for 24 h to obtain modified oxidized polysaccharide (OHA-DA).
[0095] (3) COL-MA was dissolved in PBS, and then OHA-DA was added to the COL-MA solution. After mixing evenly, a mixture of collagen and modified oxidized polysaccharide was obtained. LAP, HRP enzyme, and H2O2 were then added dropwise while stirring. After stirring for 2 minutes, the mixed solution was injected into a mold and irradiated under 405nm purple light for 1 minute to obtain the composite hydrogel in this example (denoted as COL-MA / OHA-DA); wherein the mass percentage of COL-MA in the mixture of collagen and modified oxidized polysaccharide was 1%, and the mass percentage of OHA-DA was 5%.
[0096] Comparative Example 2
[0097] A 3D printed bracket, the preparation method of which comprises the following steps:
[0098] (1) Weighing PLGA into the barrel, compacting it, and installing a needle (0.3 mm), and then loading it into the 3D printer;
[0099] (2) PLGA was printed into a porous scaffold (layer height 0.4 mm, pore diameter 1 mm) by 3D printing to obtain a 3D printed scaffold (denoted as PLGA).
[0100] It is understandable that the 3D printed brackets in Examples 1 to 5 are printed using conventional methods, and the specific steps can refer to Comparative Example 2.
[0101] Result detection
[0102] Taking Example 1 as an example, it is compared with the materials of the comparative example, and the characterization or test results are as follows:
[0103] 1. Morphology characterization
[0104] The hydrogel in Comparative Example 1 (COL-MA / OHA-DA) was freeze-dried at -20°C for 48 h, and then its surface morphology was observed using an electron microscope. Figure 1 (a) and Figure 1 (b) As shown in the figure. As can be seen from the figure, the hydrogel in Comparative Example 1 presents a porous structure after freeze-drying, and most of the pore diameters are about 100 μm. This morphology is conducive to cell adhesion and cartilage promotion. The preparation method of the hydrogel in Comparative Example 1 is the same as the hydrogel used in the composite scaffold of Example 1. This also shows that in the composite scaffold of Example 1 of the present invention, the hydrogel also presents a porous structure with a pore diameter of about 100 μm, which is conducive to cell adhesion and cartilage regeneration. At the same time, the morphology of the 3D printed PLGA scaffold (Comparative Example 2) without hydrogel injection was characterized, as shown in FIG. Figure 1As shown in (c) (the scale bars of the electron microscope images are 1 mm and 500 μm, respectively), the composite scaffold of Example 1 has a uniform pore structure, which is conducive to the perfusion of the hydrogel. The PLGA scaffold used in the composite scaffold of Example 1 is the same as that of Comparative Example 2, that is, the PLGA scaffold has the same structural characteristics. In addition, the morphological characteristics of the composite scaffold of Example 1 are as follows: Figure 1 As shown in (d) (the scale bar of the electron microscope images is 200 μm), Figure 1 (d) It can be seen that in the composite scaffold, the hydrogel is well filled in the 3D printed PLGA scaffold.
[0105] The cartilage regeneration composite scaffolds of Examples 2 to 5 also have a porous structure, and the hydrogel is well filled in the 3D printed scaffold.
[0106] 2. Compression strength
[0107] The compressive strength tests of the composite scaffold (PLGA / COL-MA / OHA-DA) of Example 1, the hydrogel (COL-MA / OHA-DA) of Comparative Example 1, and the scaffold (PLGA) of Comparative Example 2 were performed using a universal mechanical testing machine. The test conditions were 1 mm / min. The test results are shown in FIG. Figure 2 As shown. Figure 2 As can be seen, the compressive strength of the PLGA / COL-MA / OHA-DA composite scaffold in Example 1 increases with increasing strain rate, reaching a mechanical property of 4.37 MPa at 8.5% strain. The mechanical property of the COL-MA / OHA-DA composite scaffold in Comparative Example 1 is within 1 kPa at 10% strain, and the mechanical property of the PLGA scaffold in Comparative Example 2 is 2.19 MPa at 5.5% strain. This demonstrates that the present invention, through the combination of a specific hydrogel and a 3D-printed scaffold, can provide improved mechanical properties and toughness to a certain extent.
[0108] 3. In vivo degradation performance
[0109] The PLGA / COL-MA / OHA-DA composite scaffold in Example 1 was implanted subcutaneously in SD rats for in vivo degradation testing. The degradation was observed at predetermined times of 4 weeks (4W), 8 weeks (8W), 12 weeks (12W), and 16 weeks (16W). The specific test diagram is shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the composite scaffold can be observed in the first three months (12 weeks), but no obvious composite scaffold is seen in the fourth month, indicating that the composite scaffold obtained by the present invention degrades subcutaneously within 3 to 4 months and has good degradability.
[0110] 4. In vitro cytocompatibility
[0111] After sterilizing the materials of Example 1 (PLGA / COL-MA / OHA-DA) and Comparative Example 2 (PLGA), the materials were placed in a 37°C incubator for extraction for 24 hours. Mouse bone marrow mesenchymal stem cells were then implanted in the material extracts and cultured for 1 and 3 days, respectively. CCK-8 working solution was then added. After incubation in a cell incubator for 1 hour, the absorbance (OD value) of each well was measured at a wavelength of 450 nm using a microplate reader. The resulting cell compatibility test graph is shown in FIG. Figure 4 shown. Figure 4 The CON group was a blank control group without the addition of the extract. Figure 4 It can be seen that on the 1st and 3rd day of culture, both groups of materials have good proliferation effects, and the proliferation effect of Example 1 is significantly better, indicating that the composite scaffold of the present invention has good cell compatibility.
[0112] It should be understood that the composite scaffolds of Examples 2 to 5 have the same structure and similar components as that of Example 1, and also have good cell compatibility.
[0113] In summary, the composite scaffold provided by the present invention has excellent mechanical properties, degradability and biocompatibility, high compressive strength, and can adjust the cross-linking degree and degradability of the hydrogel by controlling the photoreaction and enzyme cross-linking reaction to meet different cartilage repair needs. It also has the advantage of promoting cartilage repair and can be implanted as a cartilage regeneration material into the cartilage damage site for repair, which is beneficial to the effective and rapid regeneration of cartilage defects and has broad application prospects.
[0114] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be considered as equivalent replacement methods and are included in the scope of protection of the present invention.
Claims
1. A composite stent, characterized in that: It comprises a scaffold and a hydrogel; the raw materials for preparing the hydrogel comprise photosensitive collagen and modified oxidized polysaccharide; and the hydrogel is filled in the scaffold.
2. The composite stent according to claim 1, characterized in that: The mass ratio of the photosensitive collagen to the modified oxidized polysaccharide is (0.1-10): (0.1-20).
3. The composite stent according to claim 1 or 2, characterized in that: The photosensitive collagen includes at least one of methacrylated collagen and glycidyl methacrylated collagen; the collagen includes at least one of animal-derived collagen, type I collagen, type II collagen, and type III collagen; And / or, the modified oxidized polysaccharide includes at least one of modified oxidized hyaluronic acid, modified oxidized chondroitin sulfate, modified oxidized chitosan, and modified oxidized sodium alginate.
4. The composite stent according to claim 1 or 2, characterized in that: The modifying agent of the modified oxidized polysaccharide includes at least one of dopamine and methacrylic acid; And / or, the modified oxidized polysaccharide is prepared by a method comprising the following steps: oxidizing the polysaccharide and then mixing it with a modifier for modification to obtain the modified oxidized polysaccharide.
5. The composite stent according to claim 1 or 2, characterized in that: The photosensitive collagen is prepared by a method comprising the following steps: collagen is mixed with a double bond modifier for reaction to obtain the photosensitive collagen; the double bond modifier comprises at least one of methacrylic anhydride and glycidyl methacrylate.
6. The composite stent according to claim 1, characterized in that: The bracket is a 3D printed bracket; And / or, the composition of the scaffold includes at least one of polylactic acid, polycaprolactone, polylactic acid-glycolic acid copolymer, polyglycolic acid, poly (3-hydroxybutyric acid-co-3-hydroxyvalerate), poly-β-hydroxyalkanoate, and polycitric acid.
7. A method for preparing the composite stent according to any one of claims 1 to 6, characterized in that: The following steps are involved: The photosensitive collagen and the modified oxidized polysaccharide are mixed and subjected to an enzyme cross-linking reaction; the mixture obtained by the enzyme cross-linking reaction is injected into the stent and subjected to a photoreaction to obtain the composite stent.
8. The preparation method according to claim 7, characterized in that: The illumination wavelength of the photoreaction is 365-420nm; And / or, the light reaction time is 30s to 40min; And / or, the time of the enzyme cross-linking reaction is 30s to 30min.
9. The preparation method according to claim 7, characterized in that: The cross-linking agent of the enzyme cross-linking reaction includes at least one of peroxidase, transglutaminase, lysine oxidase and hydrogen peroxide; And / or, the photoreaction photoinitiator includes at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and phenyl di (2,4,6-trimethylbenzoyl) phosphine oxide.
10. Use of the composite scaffold according to any one of claims 1 to 6 or the composite scaffold obtained by the preparation method according to any one of claims 7 to 9 in preparing cartilage regeneration materials.